(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the immediate effects of diaphragmatic breathing and pursed lip breathing exercise on blood pressure, pulse rate and oxygen saturation in hypertensive people. Study Design: Randomized Clinical Trial Place and Duration of Study: This study was conducted at the Community Dwelling Areas of Lahore Study was completed in 6 months from December, 2020 to June, 2021. Materials and Methods: One group was given diaphragmatic breathing exercise (DBE) and other was instructed pursed lip breathing exercise (PLBE). Pre and Post treatment values of blood pressure(BP), pulse(PR) and oxygen saturation(PSO2) were recorded. Results: In across the group comparison both groups showed significant changes after treatment with p<0.05. Conclusion: Diaphragmatic breathing and pursed lip breathing are equally effective in decreasing BP, HB and surging PSO2.